1992
DOI: 10.1161/01.res.71.5.1088
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor suppresses and fibroblast growth factor enhances cytokine-induced production of nitric oxide by cultured smooth muscle cells. Effects on cell proliferation.

Abstract: Stimulation of thymidine incorporation by basic fibroblast growth factor or epidermal growth factor treatment of cultured quiescent smooth muscle cells (rat and human) was attenuated by the concomitant treatment with interleukin-1 beta in the presence of indomethacin. Platelet-derived growth factor-AB and -BB-induced thymidine incorporation was not inhibited by the presence of the cytokine under similar experimental conditions. Elevation of nitrite levels in the conditioned medium of cultures exposed to interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(78 citation statements)
references
References 40 publications
2
75
0
1
Order By: Relevance
“…Results of some of these studies [16,17], by indicating that co-stimulation of mesangium with IL-1 and TNF-acts synergistically to generate large amounts of nitrite, prompted us to utilize concurrently both cytokines in our experiments. MC stimulated to proliferate with bFGF did not in our hands respond as vigorously by production of nitrite to stimulation with IL-1 and TNF-as did quiescent cells, contrary to vascular smooth muscle cells, which more remarkably enhance generation of NO 2 -upon triggering with IL-1 and bFGF, as described by Scott-Burden et al [19]. This difference in reactivity to proinflammatory cytokines may indicate that MC, as specialized glomerular pericytes, may have a greater potential to secrete NO in response to inflammatory stimuli than their less differentiated counterparts in blood vessels of higher calibre.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Results of some of these studies [16,17], by indicating that co-stimulation of mesangium with IL-1 and TNF-acts synergistically to generate large amounts of nitrite, prompted us to utilize concurrently both cytokines in our experiments. MC stimulated to proliferate with bFGF did not in our hands respond as vigorously by production of nitrite to stimulation with IL-1 and TNF-as did quiescent cells, contrary to vascular smooth muscle cells, which more remarkably enhance generation of NO 2 -upon triggering with IL-1 and bFGF, as described by Scott-Burden et al [19]. This difference in reactivity to proinflammatory cytokines may indicate that MC, as specialized glomerular pericytes, may have a greater potential to secrete NO in response to inflammatory stimuli than their less differentiated counterparts in blood vessels of higher calibre.…”
Section: Discussionsupporting
confidence: 66%
“…Garg & Hassid have documented inhibition of mesangial proliferation by NO donor vasodilators, but cell viability was not adversely affected by NO in their study [12]. Further down this line, Scott-Burden et al reported [19] that levels of nitrite released by vascular smooth muscle cells in response to IL-1 correlated with the inhibition of thymidine incorporation. On the other hand, in a recent report Mohaupt et al [20] demonstrated lack of significant antiproliferative effect of autocrine (IL-1 -stimulated), or exogenous NO on cultured rat MC.…”
Section: Discussionmentioning
confidence: 86%
“…Infiltrating activated macrophages release interleukin-ll3 (IL-I[~) and tumor necrosis factor (TNF-~), which induce the macrophage-type NO synthase (iNOS or NOS II) in mesangial cells (MCs) [3,4]. The induction of iNOS is regulated not only by these inflammatory cytokines and endotoxin but also by other factors, such as cAMP-elevating agents [5,6] and basic fibroblast growth factor [7]. In-*Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…30 In VSMCs, iNOS can be upregulated by damage or removal of the endothelium 31,32 as well as by endotoxins, such as bacterial LPS, and cytokines. 19,22,[33][34][35][36][37][38][39] The intracellular signal transduction mechanisms involved in the expression of iNOS are not completely known. Studies in macrophages, in which the regulation of iNOS expression…”
mentioning
confidence: 99%
“…30 In VSMCs, iNOS can be upregulated by damage or removal of the endothelium 31,32 as well as by endotoxins, such as bacterial LPS, and cytokines. 19,22,[33][34][35][36][37][38][39] The intracellular signal transduction mechanisms involved in the expression of iNOS are not completely known. Studies in macrophages, in which the regulation of iNOS expression has been more extensively studied, have shown that induction of iNOS by LPS or cytokines involves the activation of transcription factor NF-B, [40][41][42] which has been shown to have a binding site on the iNOS gene promoter.…”
mentioning
confidence: 99%